Legal Culture - Ansolabehere, Karina (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
This paper proposes a definition of the concept of "legal culture" that starts with the approach of which different actors serve, in different spaces, to learn the concept of Law in a specific moment and related to a specific society. Thus conceived, the concept is necessarily plural: we encounter so many legal cultures as juridical approaches that we are able to identify therefore it is proposed to consider the legal culture as an approach rather than a concept. On this basis, the author examines, on the one hand, the different doctrinal proposals of definition of the concept, and, on the other, the diverse concerns which have prompted researchers to focus, always from the critic to legal formalism, on subjects that could be regionally classified.
Keywords: Experience of law; identity of the legal system; law and society; legal formalism; culture and law